(untitled) (Ozone Therapy Global Journal, 2020)
Ozonized Saline Solution (O3SS) in one of the systemic routes of ozone administration that has been used for more than 40 years, mainly in Russia. The application protocol must be carried out under established parameters to achieve therapeutic efficacy and prevent side effects. The purpose of this paper is to study the concentrations of ozone in saline solution during the bubbling stage to establish the optimal saturation time and to study the degradation of ozone in it over time, thus defining the need for continued bubbling during reinfusion to the patient. The O3SS preparation process was simulated using a certified kit, working at the concentrations of 1 and 5 µg / NmL and the variation of the ozone concentrations in solution was determined using the spectrophotometric method. The optimum bubbling time for saturation was estimated to be 15 min and at this time 10% of the initial ozone concentration is reached in the solution. It was found that due to the accelerated degradation of O3 in saline solution, it is necessary to continue bubbling the ozone until 50 mL of saline solution remain in the container. As the western generators lacked ozone emissions in fractions of µg/NmL, it was estimated that the concentrations of 1, 2 and 5 µg/NmL at the generator outlet would be optimal for applying the low, medium and high doses required by the O3SS application according to the type of indication. ..